Penerapan Algoritma Dijkstra dalam Pemetaan UMKM Berbasis Android - Talenta Arta Deva Victoria; Hermansyah (Bulletin of Computer Science Research, 2023)
This study uses the Java programming language and the Android platform to map Micro, Small, and Medium-Sized Enterprises (MSMEs) in the Deli Serdang area using the Dijkstra algorithm. The purpose of this MSME mapping is to give consumers utilizing a mobile-based Geographic Information System (GIS) information about the closest location of MSMEs. A software development methodology combining quantitative and qualitative methodologies is used in this study. Data about the location of MSME's was gathered via surveys and conversations with company owners. Using SketchUp software, this data was then processed and examined in order to create a visual representation of the locations of MSMEs in the Deli Serdang region. Additionally, Java was used in the development of Android-based mobile applications to provide an interactive and user-friendly display. The location of MSMEs is listed on this application, along with suggestions for the quickest path from the user's current location to the MSMEs they wish to visit. According to the study findings, the Dijkstra algorithm has been successful in recommending the shortest route and fastest travel time to MSMEs, enabling users of this application to locate MSME sites with accuracy and speed. Additionally, users may view comprehensive details about each MSME, including a description of the company, its hours of operation, and contact information. It is anticipated that this application will improve the area of Deli Serdang's information accessibility for tourists and prospective MSME customers. Aside from that, it is envisaged that it will boost MSMEs' competitiveness and promote them while supporting regional economic expansion.